The public health potential of two popular apps to increase physical activity. (20th October 2021) - Bondaronek, P; Slee, A; Hamilton, F; Murray, E
Abstract: Background: The rise of health apps created novel prospects for public health intervention on a wide scale. Despite the popularity of publicly available physical activity (PA) apps, little is known about their effectiveness. This study aimed to investigate the potential of the apps to increase PA. The objectives were: 1) to determine the feasibility of the trial, 2) explore the effects of the apps on behavioural and psychological outcomes Methods: Feasibility randomised crossover trial of two popular apps. Inactive adults residing in London (UK) were eligible. The two interventions were: App A - 7 Minute Workout Challenge by Fitness Guide Inc., App B - One You Couch to 5k by Public Health England. After 1-week run-in period, participants were randomly allocated to one of the two assessment sequence (App A, B or App B, A). Results: Out of 104 participants who were eligible and consented, 63.5% (66/104) were enrolled and randomised. The primary analysis of the accelerometer data showed that there were no significant differences between baseline and the interventions using the continuous variables. Sixteen of 51 participants (31.4%) increased their time in moderate to vigorous PA (MVPA) by 20% from baseline following the introduction of the intervention (95% CI = 19.1% to 45.39). Self-reported PA outcomes showed significant increase and sedentary behaviour decreased. Exercise self-efficacy and intentions increased whilst PA outcome expectancy decreased. Conclusions: The impact of this two PA apps showed promising results with an impact observed for 20% increase in MVPA, self-reported PA, intentions and exercise self-efficacy. Yet, there was a variability in the outcomes observed. Key messages: This pragmatic trial with participants classed as inactive showed that physical activity apps can increase physical activity. There was a variability of the physical activity outcome and there is a need to tailor digital tools to the users to impact physical activity on a wide scale.